The Location of Pretreatment Hyperdense Middle Cerebral Artery Sign Predicts the Outcome of Intraarterial Thrombectomy for Acute Stroke. Issue 2 (7th April 2014) - Man, Shumei; Hussain, Muhammad Shazam; Wisco, Dolora; Katzan, Irene L.; Aoki, Junya; Tateishi, Yohei; Cheng‐Ching, Esteban; Hui, Ferdinand K.; Masaryk, Thomas J.; Rasmussen, Peter A.; Uchino, Ken
ABSTRACT: BACKGROUND AND PURPOSE: Intraarterial (IA) mechanical thrombectomy has an excellent recanalization rate but does not always correlate with good clinical outcomes. We aimed to investigate whether hyperdense middle cerebral artery sign (HMCAS) on preintervention nonenhanced CT (NECT) predicts IA therapy outcome for acute stroke. METHODS: Data were abstracted from our Hyperacute Ischemic Stroke database. Patients with occlusion in ICA, MCA, or MCA M2 branches who underwent IA therapy were included. RESULTS: Among 126 patients who underwent IA treatment, 64 (51%) had hyperdense M1 MCA sign (M1 HMCAS), 11 (9%) had hyperdense M2, and 51 (40%) had No HMCAS (NHMCAS).M1 HMCAS and NHMCAS group has comparable baseline stroke severity and infarct volume ( P > .05); and the differences of favorable outcome (modified Rankin Score 0‐2) at 30 days were not significant (21% vs. 30%, P = .259). For those with HMCAS, favorable 30‐day outcome was most frequent in Distal HMCAS (39%), followed by hyperdense M2 (27%), HMCAS proximal (11%), and HMCAS full length (0%). CONCLUSIONS: For acute ischemic stroke due to large vessel occlusion, the lack of HMCAS on NECT does not predict favorable outcome after IA therapy. Among those with HMCAS, proximal and longer HMCAS predicts unfavorable outcome.